A Review of Rice Grinding Machine Based on Cold Plasma Technology to Optimize Rice Husk Separation and Minimize Dust - Al-Bisyah, Annisa; Massaguni, Massriyady (UPPM Poltek ATI Makassar, 2024)
The rice milling industry has a strategic role in ensuring the availability of high quality rice for the community. However, the milling process often faces challenges, such as less than optimal separation of rice husks and high dust production which can have a negative impact on rice quality and worker health. To overcome this problem, this research reviews the use of cold plasma technology in rice grinding machines to increase the efficiency of separating rice husks while reducing the amount of dust produced. The results of the review show that the application of cold plasma technology can increase the efficiency of separating rice bran by reducing its adhesive force to rice grains, thereby producing better quality rice. Apart from that, this technology also contributes to reducing dust production, increasing energy efficiency and reducing operational costs. Even though it has various advantages, the implementation of this technology still faces challenges, such as high initial investment costs and the need for further research regarding its long-term impact on rice quality. With continued development and innovation, cold plasma technology has the potential to become an effective and sustainable solution in the modernization of the rice milling industry.